Measuring accounting performance of South African mergers and acquisitions - Mnyandu, Nozipho Phindile (My University, 2016)
This study examines long-term performance of publicly-listed South African acquiring firms that participated in Merger and Acquisition transactions. In an effort to close the gap in South African literature of long-term M&A performance, the study used key financial ratios in calculating the change of financial position before and after each M&A transaction or in other words, before and after the 2007 recession. The sample included 10 acquiring companies that performed 18 acquisitions during the period, 2007 and 2009. Subsequently, accounting performance in the form of Profitability, Efficiency, Liquidity, Leverage/Solvency and Investment ratios, were then analysed three years before and after each M&A transaction. Furthermore, the Paired Comparison Test was used to test for significant differences in ratios, between pre- and post-M&A performance of each acquirer. The results suggest that overall, Mergers and Acquisitions do not significantly improve financial performance of South African acquirers after each M&A transaction.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investment, June 2016
Keywords: Consolidation and merger of corporations--South Africa; Corporations--Accounting